Effective active vaccination against methamphetamine in female rats. (1st June 2017) - Nguyen, J.D.; Bremer, P.T.; Hwang, C.S.; Vandewater, S.A.; Collins, K.C.; Creehan, K.M.; Janda, K.D.; Taffe, M.A.
Highlights: Active immunization produces antibodies which can sequester drug in the blood. Such anti-drug immunotherapy has not been broadly tested in female rats. A vaccine prevented methamphetamine-induced hyperlocomotion in female rats. The MH6-KLH candidate vaccine is therefore effective in both sexes. Abstract: Background: Immunotherapies directed against methamphetamine (MA) abuse have shown success in rodent models, however only a limited number of studies have investigated active vaccination in female mice and none in female rats. It is critical to determine if potential immunotherapeutic strategies generalize across sex, particularly for drugs that may produce significant sex-differences on behavioral or physiological endpoints. Methods: Female Wistar rats were initially vaccinated with keyhole-limpet hemocyanin (KLH) or an anti-methamphetamine-KLH conjugate (MH6-KLH) three times over five weeks and implanted with radiotelemetry devices to assess locomotor activity and body temperature responses to MA. Rats were first exposed to MA via vapor inhalation (100 mg/mL in propylene glycol) and then by injection (0.25–1.0 mg/kg, i.p.) and vapor after a final vaccine boost. Results: The MH6-KLH vaccine generated an increase in antibody titers across the initial 6-week, 3 immunization protocol and a restoration of titer after a week 14 booster. Locomotor stimulation induced by 0.25 mg/kg MA, i.p, in the KLH group was prevented in the MH6-KLH group. MH6-KLH animals also exhibited an attenuated locomotor stimulation produced by 0.5 mg/kg MA, i.p. No group differences in locomotion induced by vapor inhalation of MA were observed and body temperature was not differentially affected by MA across the groups, most likely because vapor inhalation of MA that produced similar locomotor stimulation resulted in ∼10-fold higher plasma MA levels. Conclusions: This study confirms the efficacy of the MH6-KLH vaccine in attenuating the effects of MA in female rats.